Bumdes Loan And Payment Apllication At The Bandar Telu Plantation Village Office Is Website-Based - Awaliyana, Qurani; Ikhwan, Ali (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
The aim of this research is to obtain a lending and payment application that can be applied to the Bandar Telu Plantation BUMDes. This research uses the RnD research method and the Waterfall development method. Data collection was carried out by means of observation, interviews and literature study. This results of this research show that BUMDes was established to help the community meet their needs by borrowing from the community. The websote-based application for borrowing and payment for the BUMDes Plantation Village in Bandar Telu produces an application that can be accessed by administrators or members. Where the management uses a website based system, and members use a mobile-based system that can be accessed via the internet and applications. With this application, it can make it easier for administrators and members to obtain information about ongoing loans and payments, so that there is no longer a need for general ledger recapitulation which is at risk of errors in calculating interest or accumulating the amount of members bills.